A novel quantitative method for recovering precipitated uric acid in urine and analysis by LC–MS/MS. (March 2017) - Sun, Lifang; Zhou, Dongmei; Wilson, David M
Aim: Precipitation of uric acid (UA) in human urine had caused poor recovery and underestimation of UA in study samples.Results: A UA recovery method was developed for analyzing frozen urine samples that potentially contain precipitated UA. Samples were treated with 3% v/v of a solution containing 8 M potassium hydroxide and 20% v/v of ammonium thioglycolate. The high pH enables rapid dissolution of UA crystals, while the thioglycolate protects UA from oxidation at high pH. The treated samples were diluted 20-fold with 50 mM ammonium chloride and analyzed immediately by LC–MS/MS or stored at -20°C prior to analysis.Conclusion: Complete recovery of UA was achieved. Thioglycolate stabilized UA at pH 13 for at least 4.5 h at room temperature. Both accuracy and precision satisfy US FDA bioanalytical method validation (BMV) guidelines.